La place de l’alimentation dans la pensée géographique : une analyse à partir de Max Sorre et de Josué de Castro - Ana Letícia Espolador Leitão (Confins)
This article comes from the doctoral thesis “O lugar do alimento no pensamento geográfico: uma análise a partir de Max. Sorre e de Josué de Castro” (defended in September 2021 at UFES (Universidade Federal do Espírito Santo)) that presents how food has been studied in geography, starting from two authors who have intensely devoted themselves to this theme: Josué de Castro and Max Sorre. Josué de Castro is a Brazilian doctor and geographer who, since the 1940s, has effectively studied hunger in the light of his studies on food. The second is a classical geographer of French nationality and heir to the ideas of Paul Vidal de la Blache, author, among other works, of “Les Fondements de la géographie humaine”. Sorre concluded his geographical studies with “L’Homme sur la Terre : traité de géographie humaine”, including food and the geography of food in several of his studies, as well as the issue of hunger introduced to the scientific world by Josué de Castro. Based on documentary research, bibliographic readings and interviews, we show the importance of the theme of food, especially in an era that precedes the revolution of information and communication technologies, the Green Revolution and the post-Cold War period, marked by a significant increase in food production and global paradigm changes. We defend the need for a true interdisciplinarity and humanization of the humanities, also defended by these two humanist geographers. Our main objective is to share the contributions of Josué de Castro and Max Sorre in French in order to better understand the problems they observed and analysed and the continuation of their ideas after their death. We conclude that the theme is still relevant and requires efforts to eliminate the scourge already denounced by Castro in the first three quarters of the 20th century, and which continues to devastate, in an absolute and hidden way, a large part of humanity.